Praktik Penghindaran Pajak oleh Foreign Direct Investment Berbentuk Perseroan Terbatas Penanaman Modal Asing - Ning Rahayu (Universitas Riau, 2010)
The increase of Foreign Direct Investment (FDI) was improved greatly year to date in ourcountry. Despite of the positive development, there was anomalous condition in Indonesia. On theone side, the Indonesian government seriously done huge efforts to increase FDI realization withspecial facilities, but on the other side, many foreign companies in terms of Foreign InvestmentCompany did not pay Corporate Income Tax and file Income Tax Return which shown a tax loss forlong times. Those anomalous phenomenon was occured hypothetically due to the practice of taxavoidance by those companies policy. This research aim to capture practice of tax avoidance by theForeign Investment Company. The research methods using qualitative instrument and participa-tory observations. Qualitative instrument includes indepth interview with the key informants. Thisresearch result indicates there are five practices of tax avoidance which commonly performedthrough a scheme of transfer pricing, thin capitalization, treaty shopping, controlled foreign corpo-ration (CFC), and the use of tax heaven countries. Those tax avoidance practice was occured byusing the loopholes of Indonesian tax regulation. Another result of this research also depicts ourunderstanding on the close relationship between subsidiary company with its parent company abroad.For further research as theoritical implication, next researcher should be able to combine quantiativeas well as qualitative method in order to have robust research result and rigor recommendation.